Movilidad estudiantil y su influencia en las competencias del egresado del estudiante de la Facultad de Ciencias Económicas y de Negocios de la Universidad Nacional de la Amazonía Peruana 2008 – 2018 - Saavedra Perea, Rubela (2025)
The general objective of this study was to determine the relationship between student mobility and graduate competencies in the Faculty of Economics and Business at the National University of the Peruvian Amazon in the period of 2008- 2018. The study is applied, as it not only relies on descriptions but also explains in detail the relationship between the variables with a population a sample of 65 graduates. The data collection technique used was a survey, and a questionnaire to gather data. The results indicate that student mobility has a significant impact on the development of graduate competencies. In particular, the constant value was found to be 0.667, with a standard error of 0.237, suggesting that in the absence of student mobility, the baseline level of graduate competencies is 0.667. The t-value of 10.325 and the significance level of p = 0.000 confirm that this impact is statistically significant. It is concluded that there is a significant relationship between student mobility and graduate competencies in the study population. This is reflected in the positive and significant coefficient obtained, highlighting the importance of promoting mobility programs to enhance the quality of professional training.